A case of sarcoidosis‐like reaction associated with immune checkpoint inhibitors in metastatic renal cell carcinoma. Issue 1 (24th September 2021) - Katagiri, Akiyoshi; Yamazaki, Hiroyuki; Ikeda, Taro
Abstract : Introduction: Immune checkpoint inhibitors are one of the standard treatments for metastatic renal cell carcinoma. Among immune‐related adverse events, the sarcoidosis‐like reaction is frequently difficult to differentiate from cancer progression. Case presentation: A 58‐year‐old man with renal cell carcinoma with multiple lung metastases was treated with ipilimumab and nivolumab after nephrectomy. Computed tomography after three courses of treatment revealed hilar/mediastinal lymphadenopathies, pleural nodules, and pulmonary interstitial lesions, whereas lung metastases were markedly regressed. Considering positive findings of Gallium scintigraphy and serological tests together, we clinically judged the new lesions as a sarcoidosis‐like reaction and continued the treatment until cessation by liver dysfunction. After discontinuation of the immunotherapy, the sarcoidosis‐like reaction was regressed without cancer relapse. Conclusion: We report here the first case of a clinically diagnosed sarcoidosis‐like reaction in metastatic renal cell carcinoma following treatment with immune checkpoint inhibitors.